The Influence of Sustainability Reports on Financial Performance in Banking Companies Listed on the Indonesia Stock Exchange (IDX) for the 2016-2023 Period - Zulkarnaini; Ni Utami; Antaiwan Pranogyo; Ni Andini (Penerbit Jurnal Indonesia, 2025)
This study aims to determine the impact of sustainability reports, which are described in three dimensions of disclosure: Social, Environmental, and Economic, on financial performance by using profitability ratios proxied by the ROA ratio and adding company size as a control variable. The population in this study consists of banking companies listed on the Indonesia Stock Exchange that disclosed Sustainability Reports using the GRI G4 standard during the period 2017-2023. The results obtained are that the dimensions of social and environmental disclosure have a negative insignificant effect on financial performance, while the dimension of economic disclosure has a significantly positive effect on financial performance. The addition of company size as a control variable does not affect the obtained results. The results of this study can be used by investors in making investment decisions, especially by considering the sustainability report variable.